(untitled) (Andamios, Revista de Investigación Social, 2011)
This article intends to review critical theory that Jürgen Habermas gives us his theory of communicative action to display the tension between the world of life and system concepts. While Habermas argues that both dimensions are autonomous, try to demonstrate the difficulty viewing a community of communication free domain. Relations of power between humans are part of their culture, habits and even language. It is very difficult to make a criticism of the system, when it is already present in the world of life. Although it seems to me essential, rescue of Habermas’s contributions to the pragmatic turn in the philosophy of language to think policy, I think also, that his theory of communicative action continuous anchored in the illustrated tradition that trusts that humans are able to govern a reason that put them safe from the power and domination.